Application of Bailer Technique for Idle Well Reactivation in Mature Fields: Case Study of SLF Field Sumatera - Hani, Berkah; Sutresno, Wahyu (Scientific Contributions Oil and Gas, 2025)
This paper presents a field trial of wireline bailer cleanout to reactivate an idle oil well (SLL-06) in the mature SLF Field, South Sumatra Basin. The well had been shut in for several years due to severe debris accumulation and scale deposition. A low-capital bailer operation was used to remove wellbore obstructions and restore fluid communication. Eight successive bailer runs were conducted, and debris volume was quantified for each run. Results show a pronounced decline in recovered debris per run and an estimated cumulative removal of approximately 80% of the original obstruction. Post-cleanup measurements indicate a significant reduction in static fluid level of about 35% and a stabilized bottom-hole pressure (SBHP) profile, suggesting partial restoration of reservoir–wellbore connectivity. Following the intervention, the well resumed production at a low oil rate. A simplified economic assessment shows that the bailer operation required only 15–20% of the capital cost of a conventional workover. Under a conservative production assumption of approximately 30 bbl/d and an oil price of USD 70/bbl, the projected first-year revenue substantially exceeds the intervention cost. These findings confirm that wireline bailer cleanout is a technically practical and economically attractive first-step strategy for reactivating marginal wells where conventional artificial lift options are not economically viable.